STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA BULO DI MINAHASA UTARA - Ruslani, Ruslani; Alexander, Nelson; Lagarense, Bet El Silisna; Moon, Helena (Jurnal Ilmu Pariwisata, 2025)
This study aims to analyze community empowerment strategies in the development of Bulo Tourism Village, located in North Minahasa Regency, North Sulawesi. Bulo Village possesses distinctive natural and cultural potential; however, its management remains suboptimal due to limited resources and infrastructure. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The primary informants include village officials and local community members. Data analysis was conducted using the SWOT technique (Strengths, Weaknesses, Opportunities, Threats) to identify internal and external factors influencing tourism village development. The findings indicate that the main strengths lie in the village’s natural potential and community participation, while weaknesses include the lack of training and tourism promotion. Opportunities are present through government support and the growing trend of nature-based tourism, while threats come from competition with other tourism villages and dependency on external assistance. Based on the SWOT analysis, the recommended strategies include maximizing local potential through community training, strengthening tourism village institutions, establishing partnerships with external stakeholders, and enhancing digital-based promotion. These strategies are expected to sustainably strengthen community empowerment and improve the competitiveness of Bulo Tourism Village.Keywords: Analysis, Strategy, Empowerment, Community, SWOT